2019
DOI: 10.1073/pnas.1819992116
|View full text |Cite|
|
Sign up to set email alerts
|

Gene-edited stem cells enable CD33-directed immune therapy for myeloid malignancies

Abstract: Antigen-directed immunotherapies for acute myeloid leukemia (AML), such as chimeric antigen receptor T cells (CAR-Ts) or antibody-drug conjugates (ADCs), are associated with severe toxicities due to the lack of unique targetable antigens that can distinguish leukemic cells from normal myeloid cells or myeloid progenitors. Here, we present an approach to treat AML by targeting the lineage-specific myeloid antigen CD33. Our approach combines CD33-targeted CAR-T cells, or the ADC Gemtuzumab Ozogamicin with the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 27 publications
(33 reference statements)
2
73
0
Order By: Relevance
“…Recent preclinical studies have also explored the possibility of using gene-edited stem cells to enable CD33-directed immunotherapies in AML 247 . Interestingly, preliminary preclinical studies of GO in CML LSCs showed efficacy 248…”
Section: Table Of Contents Summarymentioning
confidence: 99%
“…Recent preclinical studies have also explored the possibility of using gene-edited stem cells to enable CD33-directed immunotherapies in AML 247 . Interestingly, preliminary preclinical studies of GO in CML LSCs showed efficacy 248…”
Section: Table Of Contents Summarymentioning
confidence: 99%
“… 6 8 In addition, patients affected by acute myeloid leukemia could benefit from a combination of allo-HSC transplantation and gene therapy, via the editing of the myeloid marker CD33 in donor HSCs, in order to confer resistance to anti-CD33 targeted chemotherapy. 9 11 …”
mentioning
confidence: 99%
“…For instance, both healthy and cancerous myeloid cells express CD33 and therefore traditional CD33 CAR T-cell therapy of acute myeloid leukemia (AML), which is in phase I and I/II clinical trials, would disrupt non-cancerous normal cells too [ 115 , 116 ]. Whereas tumor-specific antigen has not been identified for many tumors like some types of AML [ 117 ], and in order to prevent previously described on-target, off-tumor occurrence, two studies have demonstrated that baring the hematopoietic stem and progenitor cells from CD33 using CRISPR-Cas9 and successful transplantation of these CD33-knockout cells resulted in the safe and fully on-target, on-tumor activity of CD33-targeted CAR T-cells against AML [ 118 , 119 ]. On the other hand, CD7 is a specific potential target for AML cells, but is observed in about 30% of all patients.…”
Section: The Deluxe Zone Of Cancer Therapy Where Crispr Meets Immunomentioning
confidence: 99%